2020
DOI: 10.1037/sah0000176
|View full text |Cite
|
Sign up to set email alerts
|

Sexual minority quality of life: The indirect effect of public stigma through self-compassion, authenticity, and internalized stigma.

Abstract: Sexual minorities, or those who do not identify as straight, experience stigma that has been associated with a number of health issues and decreased quality of life. The current study expands on previous explanations of the relationship between stigma experienced by sexual minorities and quality of life by examining self-compassion and authenticity as potential mediators. We proposed and examined a mediation model in which self-compassion and authenticity would explain the relationship between stigma and quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
1
15
1
Order By: Relevance
“…Two studies that included measures of both proximal and distal minority stress tested serial mediation models. Fredrick et al (2020) demonstrated a significant indirect effect of public stigma on quality of life through internalized stigma and self-compassion in a sample of SGM participants. Similarly, Liao et al (2015) demonstrated an indirect effect of perceived discrimination on psychological distress through expectations of rejection and self-compassion.…”
Section: Resultsmentioning
confidence: 90%
“…Two studies that included measures of both proximal and distal minority stress tested serial mediation models. Fredrick et al (2020) demonstrated a significant indirect effect of public stigma on quality of life through internalized stigma and self-compassion in a sample of SGM participants. Similarly, Liao et al (2015) demonstrated an indirect effect of perceived discrimination on psychological distress through expectations of rejection and self-compassion.…”
Section: Resultsmentioning
confidence: 90%
“…In other words, for this population, shaming traumatic homophobic experiences seem to impact psychopathology partially through the lack of compassionate actions. In fact, self-compassion has been indicated as a positive psychological process for well-being in this population [ 70 , 71 , 72 ]. These results seem consistent with other studies that presented negative and moderate correlations between shame and self-compassion [ 50 ], including other minority populations (e.g., people living with HIV) [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that holding a positive SGM identity may protect mental health in the face of adverse experiences related to stigma against SGM. SGM authenticity has been found to buffer the effects of externalized stigma on quality of life in sexual minoritized adults (Fredrick et al, 2020). Woulfe and Goodman (2020) found that identity affirmation moderated the association between SGM identity abuse (e.g., someone threatening to out you) and depression, such that identity affirmation was protective against the depressive effects of identity abuse for SGM adults.…”
Section: Minoritized Stress and Mental Healthmentioning
confidence: 99%